2016
DOI: 10.1038/srep20572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high CO2 on the geochemistry of the coralline algae Lithothamnion glaciale

Abstract: Coralline algae are a significant component of the benthic ecosystem. Their ability to withstand physical stresses in high energy environments relies on their skeletal structure which is composed of high Mg-calcite. High Mg-calcite is, however, the most soluble form of calcium carbonate and therefore potentially vulnerable to the change in carbonate chemistry resulting from the absorption of anthropogenic CO2 by the ocean. We examine the geochemistry of the cold water coralline alga Lithothamnion glaciale grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 51 publications
10
53
3
Order By: Relevance
“…Here, we have presented quite similar relationships for Mg content and anatomy in Phymatolithon as has been found in Lithothamnion glaciale (Ragazzola et al. ) and P. onkodes (Nash ). All species have elevated Mg in cell walls compared to interfilament.…”
Section: Discussionsupporting
confidence: 85%
“…Here, we have presented quite similar relationships for Mg content and anatomy in Phymatolithon as has been found in Lithothamnion glaciale (Ragazzola et al. ) and P. onkodes (Nash ). All species have elevated Mg in cell walls compared to interfilament.…”
Section: Discussionsupporting
confidence: 85%
“…These Mg variations are in agreement with the Mg offsets obtained for the cell wall, IF, and hypothallial cells in Leptophytum laeve and Kvaleya epilaeve from Arctic Labrador (Nash and Adey, 2017a). The elevated Mg in perithallial cell walls compared to IF (called interstitial) has also been noted for Lithothamnion glaciale (Ragazzola et al, 2016). Climate archiving, using Mg concentration (and other wall chemistry) as a proxy for seawater temperature (and other variables) at the time of wall formation has become an important tool in paleoclimatology (e.g., Halfar et al, 2013).…”
Section: Magnesium Contentsupporting
confidence: 77%
“…Concentric zonations of higher Mg content have been shown, using backscatter electron imaging, in cell walls of tropical Porolithon onkodes (Nash et al, 2011). Ragazzola et al (2016), using NanoSIMS, also showed clear concentric banding of Mg within summer cell walls of Lithothamnion glaciale. These published observations together with the results in this study suggest there could be a strong organic control on Mg distribution within the cell, with this being related to the concentric fibrils.…”
Section: Banding and Magnesium Uptakementioning
confidence: 99%
“…Possibly the fibril organics enable higher Mg incorporation than the organics involved in the radial structures. Ragazzola et al (2016) further documented a decreased prominence of Mg banding in winter cells of L. glaciale and for those grown in CO 2 -enriched conditions. Results from our study offer an insight as to possible temperature or CO 2 -driven ultrastructure changes that may result in decreased Mg content.…”
Section: Banding and Magnesium Uptakementioning
confidence: 99%
See 1 more Smart Citation